2011
DOI: 10.1016/j.febslet.2011.06.039
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-19b downregulates insulin 1 through targeting transcription factor NeuroD1

Abstract: a b s t r a c tMiR-17-92 cluster miRNAs are disclosed to contribute to the development of multiple organs and tumorigenesis, but their roles in pancreas development remains unclear. In this study, we found that miR-19b, a member of miR-17-92, was highly expressed in the pancreatic progenitor cells, and miR-19b could target the 3 0 UTR of NeuroD1 mRNA to decrease its protein and mRNA levels. Functional analysis showed that miR-19b exerted little effect on the proliferation of pancreatic progenitors, whereas it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…Rfx6 , another Ngn3-dependent gene in endocrine cells, is under tight regulation by two glucose-regulated miRNAs, miR-30d and let-7e (Liao et al, 2013). Others have shown that miR-19b represses insulin gene transcription following engagement of its mRNA target NeuroD1 (Zhang et al, 2011). Nevertheless, a role for miR-19b, miR-30d, and let-7e during β-cell development remains to be demonstrated.…”
Section: Mirnas and The Acquisition Of β-Cell Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…Rfx6 , another Ngn3-dependent gene in endocrine cells, is under tight regulation by two glucose-regulated miRNAs, miR-30d and let-7e (Liao et al, 2013). Others have shown that miR-19b represses insulin gene transcription following engagement of its mRNA target NeuroD1 (Zhang et al, 2011). Nevertheless, a role for miR-19b, miR-30d, and let-7e during β-cell development remains to be demonstrated.…”
Section: Mirnas and The Acquisition Of β-Cell Identitymentioning
confidence: 99%
“…Specific miRNAs affect insulin production (Melkman-Zehavi et al, 2011; Zhang et al, 2011; Nieto et al, 2012; Setyowati Karolina et al, 2013; Xu et al, 2015), insulin exocytosis (Plaisance et al, 2006; Lovis et al, 2008a), growth (Tattikota et al, 2014), or apoptosis (Lovis et al, 2008b; Ruan et al, 2011). Additionally, to the best of our knowledge, the function of only four miRNAs (miR-375, miR-7a, miR-184, and the miR-200 family) has been addressed in vivo in the β-cell using mouse genetic studies (Poy et al, 2009; Latreille et al, 2014; Tattikota et al, 2014; Belgardt et al, 2015).…”
Section: Role Of Mirnas In Maintaining Mature β-Cell Identitymentioning
confidence: 99%
“…The MIN6 insulinoma cells were maintained in DMEM containing 25 mmol/L glucose supplemented with 15% FBS and 50 μmol/L 2-mercaptoethanol. Isolation of adult pancreatic progenitor cells was described in our previous report [20]. Pancreatic progenitor cells were cultured with DMEM/F12 medium containing 2% FBS and supplemented with 1×B27 (Invitrogen), 20 ng/mL EGF (R&D), 10 ug/mL insulin (Sigma-Aldrich) and 50 μmol/L 2-mercaptoethanol (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…In the group of inversely regulated miRNA-mRNA pairs, also three previously reported, edited miRNAs and their targets were found. NEROD1 (neurogenic differentiation 1) is known to be targeted by mmu-miR-19b (Zhang et al 2011), whereas the targets of the reported edited mmu-let-7g and mmumiR-153, HOXA9 (homeobox A9), and SYN2 (synapsin II) are predictions of TargetScan. The predicted target for mmu-miR-153, SYN2, is also predicted to be targeted by mmu-miR-30a-c&e as well as mmu-miR-32, all consistently up-regulated in the double knockout ( Table 2).…”
Section: Changes In Mirna Abundance Affect Potential Target Mrnasmentioning
confidence: 99%